Performance Evaluation of Vehicle Restraint Systems in the Context of Design and Installation - Shahram Tahmasseby; Deepti Muley; Bernd Wolfgang Wink (Salehan Institute of Higher Education, 2021)
Vehicle Restraint Systems (VRS), a necessary component of the road design, are widely implemented by transport authorities to protect vehicles from severe incidents, mainly colliding to the roadside as well as median obstacles and other potential hazards. The performance evaluation of vehicle restraint systems at the design and installation stages is largely made according to either European or American standards. The local traffic conditions and vehicle compositions in countries, which are noticeably different from Europe and North America, necessitate a customized guideline in which the design and installation of road safety barriers are more adapted to the local conditions of the country. This paper briefly reviews the main features of EN1317, and NCHRP 350/MASH standards, which are predominantly used for the design, installation, and performance evaluation of VRS in Europe and the United States respectively. Moreover, the contribution of these standards in developing the VRS guideline for the State of Qatar is explained. The study recommends customizations to the design and installation of VRS, which are presently implemented according to the guideline developed by the Public Work Authority in Qatar. The present guideline follows European as well as American standards. The recommendations are made based on empirical studies and evidence observed by undertaking a series of site visits, audits, and perform inspections of VRS components installed on Qatari roads and highways. The study findings demonstrate the performance of VRS can be enhanced by incorporating the design and selection of road safety components such as guardrails, terminals, transitions, and crash cushions at the preliminary design stage of roads and highways. This study brings about practical insights and implications for road designers, contractors, supervision teams, and road safety auditors. Doi: 10.28991/cej-2021-03091665 Full Text: PDF